Too big? A review of methods for removing large endometrial polyps in office minihysteroscopy – broadening the indications for the procedure in the COVID-19 pandemic - Magdalena M. Biela; Jacek Doniec; Paweł Kamiński (Videosurgery and Other Miniinvasive Techniques)
Hysteroscopy is the gold standard for the diagnosis and treatment of endometrial polyps. For small polyps (less than 2 cm) minihysteroscopy can be performed in an office setting. Patients with polyps larger than 2 cm are usually referred for a standard resectoscope procedure in the operation room (OR) under general anaesthesia. Those patients are exposed to longer hospital stay and possible complications of the anaesthesia. Furthermore, they usually have longer contact with many medical staff members. Limiting the time of contact as well as the number of staff involved in the procedure is particularly important during the COVID-19 pandemic. For this reason, minihysteroscopy in an office setting should be the first choice in every possible indication. We present the methods that may be useful for removing even large polyps in minihysteroscopy. The advantages and disadvantages of every procedure are discussed.